Qualitative and Quantitative Characterization of Secondary Metabolites of Qust' Al-Hindi (Saussurea Lappa) Plants - Nila Tanyela Berghuis; Ana Lailatul Farida; Aulia Ilmiawati (Program Studi Kimia, Universitas Lambung Mangkurat, 2023)
Utilization of plants that have the potential as herbal medicines, including the Qust' Al-Hindi (Saussurea Lappa) plant. Identification of the secondary metabolite content of the Qust' Al-Hindi Plant (Saussurea Lappa) through Phytochemical analysis in the form of flavonoid, alkaloid, steroid, terpenoid, tannin, and saponin tests on the extraction results as well as the calculation of flavonoid levels which are the largest content of this plant carried out using the UV method. -Vis. The characterization of the presence of a class of secondary metabolites contained in the plant was analyzed using FTIR-ATR spectroscopy. The results of this study indicate that the plant contains secondary metabolites in the form of flavonoid compounds, alkaloids, terpenoids, and tannins. The flavonoid content obtained was 223.33 ± 66.5 mgQE/g, while the results of the FTIR-ATR test showed that the extract contained the same functional groups as flavonoids, alkaloids, terpenoids, and tannins, namely the O-H, C-H, C=C functional groups. C=O and C-O contained in the structure of flavonoids, alkaloid compounds are known to have a distinctive functional group, namely N-H, for terpenoids to have a distinctive functional group, namely C-H, namely CH2 and CH3, there is also CH and there is a C-O group which is a typical functional group of compounds tannins.